USABILITY ANALYSIS OF CAMSCANNER APPLICATIONS USING THE SYSTEM USABILITY SCALE (SUS) METHOD - Bagas Yana Prayoga (JURNAL PERANGKAT LUNAK, 2023)
In the current digital era, technology has transformed the way we work and interact with the world around us. One significant development is the ability to convert physical documents into a digital format using scanning applications. One popular application for this task is CamScanner. This research aims to measure the CamScanner application's usability level using the System Usability Scale (SUS) analysis. The research method is a quantitative descriptive approach, aiming to provide a structured, accurate, and up-to-date understanding of the researched object. Data collection was conducted using a questionnaire created with Google Forms and distributed to 30 respondents. The findings of this research indicate that the CamScanner application exhibits usability with an acceptability level of "Acceptable," a grade of "B," and an adjective rating of "Good." This conclusion is based on calculating the average questionnaire score, which yielded a value of 74.2.